Social paediatrics. Issue 2 (13th January 2005) - Spencer, Nick; Colomer, Concha; Alperstein, Garth; Bouvier, Paul; Colomer, Julia; Duperrex, Olivier; Gokcay, Gulbin; Julien, Gilles; Kohler, Lennart; Lindström, Bengt; Macfarlane, Aidan; Mercer, Raul; et al.
Abstract : Social paediatrics is an approach to child health that focuses on the child, in illness and in health, within the context of their society, environment, school, and family. The glossary clarifies the range of terms used to describe aspects of paediatric practice that overlap or are subsumed under social paediatrics and defines key social paediatric concepts. The glossary was compiled by a process of consultation and consensus building among the authors who are all members of the European Society for Social Paediatrics. Social paediatricians from outside Europe were included giving a more international perspective.